Biomimetic echolocation with application to radar and sonar sensing - Baker, Chris J.; Smith, Graeme E.; Balleri, Alessio; Holderied, Marc W.; Griffiths, Hugh D. (IEEE, 2014)
Nature provides a number of examples where acoustic echolocation is the primary sensing modality, the most well-known of these being the bat, whale and dolphin. All demonstrate a remarkable ability to "see with sound". Using echolocation they navigate, locate and capture prey. As species, they have not only survived but have thrived in all their individual environments, often solely reliant on echolocation. All of these creatures are inherently cognitive. They all maintain a perception of their environment through the nervous system that allows them to take actions. In this paper we focus on the bat as an example of a cognitive system exploiting a memory-driven perception-action cycle, enabling it to navigate and interact with its environment. The key conceptual components of cognition and how it could be applied to man-made echoic sensors is introduced. This is followed by a description of how echoic flow fields, a bio-inspired technique that bats have been shown to use, fit guidance and control problems. We then go on to explain how bats are able to reliably distinguish between different targets. A combination of the theory and examples is used to demonstrate the vast potential for advancing the capability of made in man-made systems by adopting aspects of natural echolocating cognitive dynamic systems.
Keywords: Radar systems; Sensors